Connector sets and interconnect components to be used in optical fibre communication systems. Product specifications. Simplex and duplex cords made from simplex plugs with cylindrical ferrules, using EN 60793-2-50 single-mode B-652 ou B-657 fibre for Category C according to EN 61753-1 Part 14-1, (1st November 2021) - British Standards Institution,
No abstract available